Production of Premium Motor Spirit (PMS) Additive from Acetone and D-limonene - Francisca, Ikechukwu Ijeoma; Uchechukwu, Nwaiwu; Osaruyi, Obaseki Monday (Kathmandu University Journal of Science, Engineering and Technology, 2022)
A PMS additive containing acetone, D-limonene and a synthetic two stroke oil was produced. This additive improves the efficiency of fuel it is used in and also serves as an injector cleanser in engines due to the presence of D-limonene. This product prevents the destruction of parts of engine (metal parts and rubbers) that occurs due to ethanol softening. This invention also eradicates the chances of water collection and phase separation that is present in ethanol use. ASTM test analysis revealed that a sample of our prototype has a cloud point of 34°F, Kinematic viscosity of 4.8 mm2/s, Carbon residue of 0.2 and Research Octane number (RON) of 89. Manual test was also carried out to show the duration our PMS blended mixture which was 305 minutes and it lasts longer than pure PMS bought at a filling station which was 282 minutes.